(untitled) (Universal International Scientific Journal, 2026)
This article analyzes how cultural and arts organizations can promote gender equality, drawing on the experience of Uzbekistan. It explores specific mechanisms through which cultural institutions can transform social relations and support women and vulnerable groups through art, education, and public events. It argues that art is a valuable tool for fostering social dialogue and implementing non-violent social change.